Optimisation And Characterisation Of Functionalised Graphene Nanoplatelets Filled NR/EPDM Nanocomposites - Mahamood, Mazlin Aida (UTeM, 2016)
Nowadays, polymer nanocomposites have attracted great interest due to their outstanding improvements in material properties as compared to neat polymers or conventional composites. This research is to prepare and characterise the Natural Rubber (NR) / Ethylene Propylene Diene Monomer (EPDM) filled Graphene Nanoplatelets (GNPs) nanocomposites for mechanical and thermal performance compared than unfilled NR/EPDM blend. The stage 1 of the research is to improve the miscibility between NR and EPDM rubber phases by using MAH grafted EPM compatibiliser. NR/EPDM blends were compounded using a Haake internal mixer and vulcanised by a semi-EV curing system in accordance to ASTM D3192. The response surface methodology (RSM) by Design Expert 6.0.10 software was used to optimize an internal mixer processing parameters and amount of MAH grafted EPM compatibiliser towards the maximum tensile strength (TS). The optimum mixing parameters was mixing temperature of 110°C, rotor speed of 40 rpm, mixing period of 5 mins and 5 phr amount of MAH grafted EPM compatibiliser with the highest repeatability and R2 value of ~99.00%. The stage 2 of the research was focusing on the graphene nanoplatelets surface treatment by the non-covalent methods using polyethyleneimines (PEI) in an ethanol: distilled water medium (75:25). The physical adsorption of PEI on GNPs by non-covalent treatment was proposed as a possible interaction mechanism. During the stage 3 of this research, the effects of GNPs surface treatment and loading (0.25-5.00 wt. %) to the processability, mechanical, physical, thermal and morphological properties of the nanocomposites were studied. The surface treatment of GNPs enhanced the filler-matrices interaction in the NR/EPDM blend nanocomposites. The nanocomposites with 3.00 wt. % PEI-treated GNPs possessed outstanding mechanical properties compared to the unfilled blends and filled samples without treatment (tensile strength of 27.78 MPa, 19.65 MPa and 23.34 MPa; resepectively). The results were supported with thermal and dynamic analyses. At the last stage of the study, the superior thermal conductivity of 0.6220 Wm-1K-1 from the thermal conductivity analysis (TCA), showed that the NR/EPDM blends filled with 3.00 wt. % PEI-treated GNPs exhibited an enhancement in the heat dissipation and thermalmechanical properties in comparison to the unfilled NR/EPDM blend. In overall, NR/EPDM filled GNPs nanocomposite that was prepared through the combination of an optimized melt-blending processing parameters and amount of MAH compatibiliser with addition of PEI-treated GNPs is able to provide a maximum effects of improved mechanical and thermal properties which is beneficial for the suggested application of rubber component in an automotive engine mount.